The heightened importance of the microbiome in cancer immunotherapy. Issue 1 (January 2023) - Villemin, Clélia; Six, Anne; Neville, B. Anne; Lawley, Trevor D.; Robinson, Matthew J.; Bakdash, Ghaith
Highlights: Perturbations in human gut microbiome can be involved in cancer development, leading to the recognition of the microbiome as a new hallmark of cancer. Mouse experiments have demonstrated that tissue and tumor-resident microbiomes can contribute to tumor development at least in part by modulating immune responses towards it. Unique microbiome signatures can be potential prognostic and predictive biomarkers in human cancers. The human gut microbiome composition is a key determinant of the response to immune checkpoint inhibitor (ICI) therapy. The microbiome has a great influence on anticancer immune responses through direct contact with immune cells, or via metabolites, as reported in mouse experiments. Modulating the gut microbiome of ICI-resistant cancer patients by fecal microbiota transplantation or by defined live bacterial products has shown potential in enhancing responses to ICI treatment in cancer clinical trials. Significance: The strong influence of the microbiome on anticancer immunity has inspired a new line of bacterial-based therapies that can potentially reshape the immunological landscape around tumors, thereby enhancing responses to cancer immunotherapeutics. Abstract: The human microbiome is recognized as a key factor in health and disease. This has been further corroborated by identifying changes in microbiome composition and function as a novel hallmark in cancer. These effects are exerted through microbiome interactions with host cells, impacting a wide variety of developmental and physiological processes. In this review, we discuss some of the latest findings on how the bacterial component of the microbiome can influence outcomes for different cancer immunotherapy modalities, highlighting identified mechanisms of action. We also address the clinical efforts to utilize this knowledge to achieve better responses to immunotherapy. A refined understanding of microbiome variations in patients and microbiome–host interactions with cancer therapies is essential to realize optimal clinical responses.